Welcome to the Dark Side: Partial Nighttime Illumination Affects Night-and Daytime Foraging Behavior of a Small Mammal - Hoffmann, Julia; Hölker, Franz; Eccard, Jana A. (Frontiers in Ecology and Evolution, 2022)
Differences in natural light conditions caused by changes in moonlight are known to affect perceived predation risk in many nocturnal prey species. As artificial light at night (ALAN) is steadily increasing in space and intensity, it has the potential to change movement and foraging behavior of many species as it might increase perceived predation risk and mask natural light cycles. We investigated if partial nighttime illumination leads to changes in foraging behavior during the night and the subsequent day in a small mammal and whether these changes are related to animal personalities. We subjected bank voles to partial nighttime illumination in a foraging landscape under laboratory conditions and in large grassland enclosures under near natural conditions. We measured giving-up density of food in illuminated and dark artificial seed patches and video recorded the movement of animals. While animals reduced number of visits to illuminated seed patches at night, they increased visits to these patches at the following day compared to dark seed patches. Overall, bold individuals had lower giving-up densities than shy individuals but this difference increased at day in formerly illuminated seed patches. Small mammals thus showed carry-over effects on daytime foraging behavior due to ALAN, i.e. nocturnal illumination has the potential to affect intra- and interspecific interactions during both night and day with possible changes in personality structure within populations and altered predator-prey dynamics.